MACHINE LEARNING ALGORITHMS APPLIED ON THE KNOWLEDGE BASE OF AN ENDLESS LEARNING SYSTEM - Mario Ribeiro Neto, Amaury (2023)
NELL is a never-ending learning system that aims to have computational systems learned in a continuous and incremental way, being also able to use acquired knowledge to improve their own learning. The objective of this work is to use different machine learning techniques to build models that make inferences and generate new facts in order to populate the knowledge base of the NELL system. The generated models were trained with a database built from information from existing relationships in the NELL knowledge base and compared through evaluation metrics that resulted in good prediction and classification values.